Experimental Design Optimization of a Sequential Injection Method for Promazine Assay in Bulk and Pharmaceutical Formulations. (20th November 2007) - Idris, Abubakr M.; Assubaie, Fahad N.; Sultan, Salah M.
Abstract : Experimental design optimization approach was utilized to develop a sequential injection analysis (SIA) method for promazine assay in bulk and pharmaceutical formulations. The method was based on the oxidation of promazine by Ce(IV) in sulfuric acidic media resulting in a spectrophotometrically detectable species at 512 nm. A 3 3 full factorial design and response surface methods were applied to optimize experimental conditions potentially controlling the analysis. The optimum conditions obtained were 1.0 × 10 − 4 M sulphuric acid, 0.01 M Ce(IV), and 10 μ L/s flow rate. Good analytical parameters were obtained including range of linearity 1–150 μ g/mL, linearity with correlation coefficient 0.9997, accuracy with mean recovery 98.2%, repeatability with RSD 1.4% (n = 7 consequent injections), intermediate precision with RSD 2.1% (n = 5 runs over a week), limits of detection 0.34 μ g/mL, limits of quantification 0.93 μ g/mL, and sampling frequency 23 samples/h. The obtained results were realized by the British Pharmacopoeia method and comparable results were obtained. The provided SIA method enjoys the advantages of the technique with respect to rapidity, reagent/sample saving, and safety in solution handling and to the environment.